Comparison of liver biopsy and noninvasive techniques for liver fibrosis assessment in patients infected with HCV‐genotype 4 in Egypt. Issue 3 (30th July 2014) - Bonnard, P.; Elsharkawy, A.; Zalata, K.; Delarocque‐Astagneau, E.; Biard, L.; Le Fouler, L.; Hassan, A. B.; Abdel‐Hamid, M.; El‐Daly, M.; Gamal, M. E.; El Kassas, M.; Bedossa, P.; et al.
Summary In Egypt, as elsewhere, liver biopsy (LB) remains the gold standard to assess liver fibrosis in chronic hepatitis C (CHC) and is required to decide whether a treatment should be proposed. Many of its disadvantages have led to develop noninvasive methods to replace LB. These new methods should be evaluated in Egypt, where circulating virus genotype 4 (G4), increased body mass index and co‐infection with schistosomiasis may interfere with liver fibrosis assessment. Egyptian CHC‐infected patients with G4 underwent a LB, an elastometry measurement (Fibroscan©), and serum markers (APRI, Fib4 and Fibrotest©). Patients had to have a LB ≥15 mm length or ≥10 portal tracts with two pathologists blinded readings to be included in the analysis. Patients with hepatitis B virus co‐infection were excluded. Three hundred and twelve patients are reported. The performance of each technique for distinguishing F0F1 vs F2F3F4 was compared. The area under receiver operating characteristic curves was 0.70, 0.76, 0.71 and 0.75 for APRI, Fib‐4, Fibrotest© and Fibroscan©, respectively (no influence of schistosomiasis was noticed). An algorithm using the Fib4 for identifying patients with F2 stage or more reduced by nearly 90% the number of liver biopsies. Our results demonstrated that noninvasive techniques were feasible in Egypt, for CHC G4‐infected patients. Because of its validity and its easiness to perform, we believe that Fib4 may be used to assess the F2 threshold, which decides whether treatment should be proposed or delayed.